Comparing Clinical Outcomes of a Pharmacist-Managed Diabetes Clinic to Usual Physician-Based Care. (June 2018) - Schultz, Jordan L.; Horner, Kathleen E.; McDanel, Deanna L.; Miller, Michelle L.; Beranek, Randi L.; Jacobsen, Ryan B.; Sly, Nichole J.; Miller, Aaron C.; Mascardo, Lisa A.
Background: This study analyzed the impact of a pharmacist-managed diabetes clinic on clinical outcomes compared to usual care received from primary care providers (PCPs). This comparison may more definitively demonstrate the value of pharmacist management of chronic disease states. Methods: Retrospective observational cohort study conducted in patients referred to a pharmacist-managed pharmacotherapy (PT) clinic from July 2009 to October 2014. Results: For the primary outcome, the absolute change in A1c during the usual care phase was +1.53% (95% confidence interval [CI]: 1.10-1.96, P < .0001) versus an absolute change of −1.63% (95% CI: −1.28 to −1.97, P < .0001) in the intervention phase. For secondary outcomes, diabetes-related hospitalizations (10 vs 6, P = .104) and emergency room (ER) visits (27 vs 8, P = .049) decreased in the intervention phase compared to the usual care phase. The rate of diabetes-related interventions made per patient per year in the usual care phase was 2.7 versus 11.1 in the intervention phase ( P < .0001). Conclusion: Patients referred to the PT clinic had worsening blood glucose control prior to referral, and their control improved after referral to the clinic. Furthermore, there was an improvement in all diabetes-related outcomes in the intervention phase compared to the usual care phase.